Comparing preoperative and postoperative dexamethasone effects on analgesia duration in shoulder surgery - Cheng Xu; Chengyu Wang; Yanling Hu; Fei Gu; Jie Lu; Quanhong Zhou (iScience, 2024)
Summary: Dexamethasone is commonly used as an adjuvant to prolong peripheral nerve block analgesia, but the optimal timing is unclear. This randomized equivalence trial tested whether preoperative versus postoperative intravenous dexamethasone have equivalent analgesic effects when combined with interscalene brachial plexus block for shoulder surgery. 168 patients were randomized to receive 5 mg dexamethasone either preoperatively or postoperatively. The primary outcome was duration of analgesia, analyzed for equivalence with a 2-h margin. The mean durations were equivalent between groups (11.5 h preoperative versus 10.7 h postoperative). The confidence intervals fell within the equivalence margin. There were no other clinically significant differences in secondary outcomes like time to first analgesia, motor recovery, opioid consumption, blood glucose, or complications. In conclusion, as an adjuvant for nerve block, preoperative and postoperative intravenous dexamethasone provide equivalent analgesic duration, allowing for flexibility in clinical use. This addresses previous uncertainty about timing while demonstrating equivalent efficacy.